Environmental temperature and cloacal and surface temperatures of broiler chicks in first week post-hatch - Malheiros, R. D.; Moraes, V. M. B.; Bruno, L. D. G.; Malheiros, E. B.; Furlan, R. L.; Macari, Marcos [UNESP] (Applied Poultry Science Inc, 2000)
Adequate environmental temperature during the brooding period is very important to future broiler performance. Thus, the objective of this study was to investigate the extent to which environmental temperature affects the body weight and cloacal and surface (back, head, wing, and shank) temperatures. The study also investigated the sensible heat loss by radiation of broiler chicks reared at three environmental temperatures (35, 25, and 20 degrees C) up to 7 days of life. The results showed that chicks raised at low environmental temperature (20 degrees C) had lower body weight at 7 days of age. Birds kept at 20 degrees C also had significantly lower cloacal and surface temperatures than did other birds. The most marked difference was seen in the shanks. These findings revealed that body weight declined in chicks reared at 20 degrees C, and radiant heat loss (W) was nine times higher than for the birds kept at 35 degrees C at 7 days of age.
Keywords: broiler chicks; environmental temperature; sensible heat loss; surface temperature